Evaluation of an integrated mobile payment, ticketing and couponing solution based on NFC - Ferreira, Marta Campos (2014)
The emergence of Near Field Communication technology added more functionality to mobile phones. People can now access to new mobile services such as payment, ticketing, couponing, and control access to cars, homes and hotels. Although these services seem to complement each other, most studies have focused on the development and evaluation of each mobile service individually. In this paper, we propose an integrated mobile service solution – payment, ticketing and couponing – based on NFC. This solution was evaluated in a two-phase user study, which was run in real environment. Participants have largely appreciated the integration of tickets and discount coupons on the payment process. However, despite the integration of services being one of the strongest points of the solution, it also revealed to be one of the main challenges that any payment systems may have to address. Findings suggest that adding additional services to a solution may become very complex from a cognitive perspective.